Management of Distal Femoral Fracture with Distal Femoral Nail - Jahangir, Jabed; Hossain, Md Iqbal; Mojumder, Md Myen Uddin; Hossain, Mohammad; Hossain, Md Anwar; Uddin, Md Imroz (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Background: For a long time distal femur fracture were considered difficult to heal and often led to a degree of disability. The incidence of malunion, nonunion and infection are relatively high in many reported series. The management goal of distal femur fractures are correction of axial alignment, length, and rotation, restoration of motion and rapid union so as to return the patient to normal function. We present here result of retrograde nailing of extra-articular (AO 33A1 to A3) fractures of the distal femur using Distal Femoral Nail (DFN). Methods: In Between 2008 to 2010 total 17 patients (One lost to follow up so 16 available for final assessment) underwent open reduction and internal fixation for distal femoral fracture in Chittagong Medical College Hospital and Private Hospital in Chittagong city. There were 13 male and 3 female patients, age range from 18 years to 70 years, mean age 42.75 years. Average length of follow-up was 17.5months (12 months to 24 months). Results: Total 16 patients was available for follow up. Regular fracture healing was observed in 14 cases. Delayed union in 2 case. One patient had infection, and two patients had leg shorting of 0.5 and 1 cm. Axial misalignment (Varus/valgus angulations) was found in 4 cases (5º-10º) there were no implant failures. On the bases of a Leung score to measure functional outcome, 4 cases had excellent, 8 cases had good and 4 cases had fair result. Poor results were not seen in any patient. In this series 13 cases were satisfactory and 3 cases were unsatisfactory. Conclusion: Distal Femoral Nail is handsome tool to treat distal femoral fracture. Chatt Maa Shi Hosp Med Coll J; Vol.16 (2); July 2017; Page 44-47